2000
DOI: 10.1103/physrevb.62.8286
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion studies in nonequilibrium systems with attractive interactions

Abstract: Diffraction experiments can be used easily to measure the time evolution of a system under nonequilibrium conditions to attain a new equilibrium state and deduce ''nonequilibrium'' surface diffusion coefficients. It is not clear how the ''nonequilibrium'' diffusion coefficients extracted from such diffraction experiments should be interpreted. We study with Monte Carlo simulations the behavior of the ''nonequilibrium'' tracer and collective diffusion coefficients in a lattice-gas model with attractive nearest-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…29,30 The evolution of the structure factor during the first-order phase transition in the lattice system was used to extract diffusion coefficients at nonequilibrium conditions. 31 Several theories for ISF have been developed [32][33][34][35] that lead to very accurate results for the long time and small wave-vector tracer diffusion coefficient in the entire concentration range, however, their consequences in the nonhydrodynamic regimes have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 The evolution of the structure factor during the first-order phase transition in the lattice system was used to extract diffusion coefficients at nonequilibrium conditions. 31 Several theories for ISF have been developed [32][33][34][35] that lead to very accurate results for the long time and small wave-vector tracer diffusion coefficient in the entire concentration range, however, their consequences in the nonhydrodynamic regimes have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for a long time that such system orders under an influence of the external driving force [8,9,10]. Recently, this model has been studied intensively [11,12,13,14,15,16] in a context of latest experimental results. We describe below the process of stripe formation in a lattice model with two types of particles which do not interact via direct forces.…”
Section: Introductionmentioning
confidence: 99%
“…Among them a crucial role is played by the relevant order parameter for the underlying phase transformation. The domain growth exhibits t 1/2 dependence for a nonconserved order parameter, [4][5][6][7][8] and a t 1/3 dependence, called the Lifshitz-Slozov growth, [7][8][9][10][11] for a conserved one. Experimentally, it is found that slightly different systems either follow a t 1/2 growth law 12 or an almost diffusion-driven t 1/3 growth.…”
Section: Introductionmentioning
confidence: 99%